The euro's trade effects - Richard E. Baldwin (European Central Bank (ECB), 2006)
This paper reviews reassesses the methodology and principal findings of the “Rose effect”, i.e. the trade effects of currency union, looking at both EMU and non-EMU currency unions. The consensus estimate suggests that the euro has already boosted intra-euro area trade by five to ten percent. The paper discusses a gamut of models that might explain the Rose effect in Europe and suggests a series of empirical test that could help identify the economic mechanisms involved.
Keywords: F12; C33; E0; 330; Exchange rate volatility; Gravity Model; monetary union; Rose effect; Eurozone; Währungsunion; Handelseffekt; Wechselkurs; Volatilität; Gravitationsmodell; EU-Staaten; Welt